A new species of Echeveria (Crassulaceae) from the state of Guanajuato (Mexico) - Perez-Calix, Emmanuel (Instituto de Ecología, A.C., 1997)
Echeveria calderoniae is described as new, a plant native of the northwest of the state of Guanajuato (México). This species belongs to the section Secundae (Baker) Berger, and differs from its known components in its lanceolate and apically acute leaves.